Spatiotemporal Distribution of Halyomorpha halys (Stål) (Hemiptera: Pentatomidae) Across a Fruit and Tree Nut Agricultural Ecosystem. Issue 4 (29th May 2022) - Grabarczyk, Erin E; Cottrell, Ted E; Tillman, P Glynn
Abstract: The invasive brown marmorated stink bug, Halyomorpha halys (Stål) (Hemiptera: Pentatomidae), is a mobile, polyphagous agricultural pest that feeds on a variety of plants. In orchard systems, seasonal monitoring of adults and nymphs in fruit and nut trees and noncrop host plants in surrounding habitat can be used to identify, in time and space, areas of high-density aggregations to develop targeted pest management strategies. We explored the spatiotemporal distribution of H. halys adults and nymphs and assessed whether seasonal distribution patterns varied according to habitat. From 2018 to 2021, pheromone-baited traps were placed in orchard and noncrop plants to first document the establishment of H. halys at this site and to describe seasonal development. In addition, stink bugs were monitored weekly during 2019–2020 across a grid of baited traps placed within the orchard ecosystem. Based on grid data, we used Spatial Analysis by Distance Indices (SADIE) to identify significant clusters of H. halys and visualized aggregations with interpolated maps. Overall, the distribution of H. halys adults and nymphs were similar; both aggregated primarily in peach and adjacent woodlands followed by pecan. Timing of aggregations was consistent across years and reached the highest levels in July and August. Moreover, we document that H. halys is an established pest within this orchard ecosystem, and that noncrop host plants likely play an important role in maintaining populations of H. halys . To manage H. halys in southeastern orchard systems, growers may need to account for host plants in habitats that surround fruiting trees.